2015
DOI: 10.1042/bj20141018
|View full text |Cite
|
Sign up to set email alerts
|

High glucose induces mitochondrial dysfunction independently of protein O-GlcNAcylation

Abstract: Diabetes is characterized by hyperglycaemia and perturbations in intermediary metabolism. In particular, diabetes can augment flux through accessory pathways of glucose metabolism, such as the hexosamine biosynthetic pathway (HBP), which produces the sugar donor for the β-O-linked-N-acetylglucosamine (O-GlcNAc) post-translational modification of proteins. Diabetes also promotes mitochondrial dysfunction. Nevertheless, the relationships among diabetes, hyperglycaemia, mitochondrial dysfunction and O-GlcNAc modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 66 publications
0
34
0
Order By: Relevance
“…Neonatal rat cardiomyocytes were isolated from 1–2-day-old Sprague–Dawley rats as previously described [1, 5, 6, 12, 1821, 29, 30, 33]. NRCMs were plated at a density of 850,000 cells per ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal rat cardiomyocytes were isolated from 1–2-day-old Sprague–Dawley rats as previously described [1, 5, 6, 12, 1821, 29, 30, 33]. NRCMs were plated at a density of 850,000 cells per ml.…”
Section: Methodsmentioning
confidence: 99%
“…For gene transfer experiments, NRCMs were serum-starved overnight and then transduced with 100 multiplicity of infection (MOI) of replication-deficient adenoviruses carrying OGA gene (Ad-OGA; Vector Biolabs, Malvern, PA, USA), or null virus (Ad-Null; 1240, Vector Biolabs, Malvern, PA, USA) in serum free medium for 5 h as previously described [5, 6, 1821, 42]. Following virus treatment, NRCMs were returned to complete medium.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial dysfunction associated with increased O-GlcNAc levels has also been linked to O-GlcNAcylation of VDAC2 [79]. It should be noted however that there remains some controversy whether the adverse effects of hyperglycemia on mitochondrial function are mediated via increased O-GlcNAcylation [80]. On the other hand OGT has been shown to interact directly with complex IV in cardiac mitochondria from normal rats and this interaction is markedly decreased in mitochondria from diabetic rats [81].…”
Section: The Glcnac Pathway and Mitochondrial Function Under Stressmentioning
confidence: 99%
“…Also, they further found that heart mitochondrial respiratory chain proteins were differently O -GlcNAcylated under diabetic condition, and those changes in O -GlcNAcylation seemed to be closely related to changes in mitochondrial function, in particular respiration and ROS generation. However, there're also studies concluding that change of myocardial mitochondrial respiration induced by hyperglycemia is not related to O -GlcNAcylation [47]. …”
Section: O-glcnacylation Is Intimately Involved With Mitochondrialmentioning
confidence: 99%